Impacts of dead wood manipulation on the biodiversity of temperate and boreal forests. A systematic review. Issue 7 (20th May 2019) - Sandström, Jennie; Bernes, Claes; Junninen, Kaisa; Lõhmus, Asko; Macdonald, Ellen; Müller, Jörg; Jonsson, Bengt Gunnar
Abstract: Dead wood (DW) provides critical habitat for thousands of species in forests, but its amount, quality and diversity have been heavily reduced by forestry. Therefore, interventions aiming to increase DW might be necessary to support its associated biodiversity, even in protected forests, which may be former production forests. Our aim was to synthesize the current state of knowledge drawn from replicated experimental studies into solid quantitative evidence of the effects of DW manipulation on forest biodiversity, with a focus on protected forests. We conducted a full systematic review of effects of DW manipulation on forest biodiversity in boreal and temperate regions. We included three intervention types: creation of DW from live trees at the site, addition of DW from outside the site and prescribed burning. Outcomes included abundance and species richness of saproxylic insects, ground insects, wood‐inhabiting fungi, lichens, reptiles and cavity‐nesting birds. In total, we included 91 studies, 37 of which were used in meta‐analyses. Although meta‐analysis outcomes were heterogeneous, they showed that increasing the amount of DW ("DW enrichment") has positive effects on the abundance and richness of saproxylic insects and fungi. The positive effect on saproxylic pest insect abundance tended to be less than that on saproxylic insects in general. No significant effects were found for ground insects or cavity‐nesting birds. Although reviewed studies were mainly short term, our results support that management that increases DW amounts has the potential to increase the abundance of DW‐dependent species and, in most cases, also their species richness. Studies of burning showed positive effects on the abundance of saproxylic insects similar to those of other interventions, even though burning on average resulted in a smaller enrichment of DW amounts. Policy implications . The findings of the review suggest that manipulating dead wood (DW) can be an effective part of conservation management to support biodiversity in protected areas. The findings also indicate that the diversity of DW types is important, a mix of DW qualities should be favoured. Burning seems to be an effective method to increase biodiversity but to benefit cavity‐nesting birds, snag losses need to be minimized. Sammanfattning: Död ved utgör ett viktigt habitat för tusentals skogslevande arter men mängden, kvaliteteten och dess diversitet har kraftigt minskat på grund av skogsbruket. Aktiva åtgärder som ökar mängden död ved kan därför bli nödvändigt för att förbättra situationen för arter kopplade till död ved. Dessa åtgärder kan även bli aktuella i skyddade skogar, varav många områden utgörs av skogar som har en historik av mänsklig påverkan. Vårt syfte med denna studie var att kvantitativt sammanfatta befintlig kunskap som handlar om död ved‐manipulation och dess inverkan på biodiversitet med huvudfokus på skyddade skogar. Vi har genomfört en komplett systematisk översiktssammanfattning om effekterna av död ved‐manipulation på biodoversiteten i tempererade och boreala skogar. Vi inkluderade tre typer av aktiva åtgärder: skapande eller adderande av död ved samt naturvårdsbränning. Vi inkluderade effekterna på förekomst och artmångfald av vedlevande insekter, marklevande insekter, vedlevande svampar, lavar, reptiler och hålhäckande fåglar. Vi hittade relevanta 91 studier och 37 av dessa användes i en meta‐analys. Resultaten från meta‐analysen visade på att en ökning av död ved hade en tydlig positiv effekt på både förekomst och artmångfald av vedlevande insekter och svampar. Förekomsten av vedlevande insekter som klassades som skadegörare ökade också men inte i samma utsträckning som vedlevande insekter totalt sett. Vi hittade ingen signifikant effekt på marklevande insekter eller hålhäckande fåglar. I de flesta studier som ingick i vår studie hade det gått endast en kort tid efter den aktiva åtgärden men resultaten visar ändå på att skötsel som ökar mängden död ved har potential att öka förekomst, samt i de flesta fall, även artförekomst, av arter kopplade till död ved. Även studierna som inkluderade naturvårdsbränning ökade förekomst av vedlevande insekter, trots att mängden död ved denna skötselmetod resulterade i var ungefär hälften jämfört med de övriga åtgärderna. Riktlinjer för praktiker : Denna studie visade på att åtgärder som ökar mängden död ved kan vara en effektiv naturvårdande skötselåtgärd som ökar biodiversiteten i skyddade skogar. Resultaten indikerar även att diversiteten av den döda veden är viktig och att en mix av kvalité bör gynnas. Naturvårdsbränning verkar vara en effektiv metod för att gynna biodiversitet men för att gynna hålhäckande fåglar bör torrakor skyddas.